Effects of intratracheal budesonide during early postnatal life on lung maturity of premature fetal rabbits. Issue 1 (13th October 2017) - Li, Ling; Yang, Chen; Feng, Xiuliang; Du, Yongping; Zhang, Zhihong; Zhang, Yueping
Abstract: Aim: This study aimed to study the effects of intratracheal instillation of budesonide on lung maturity of premature fetal rabbits. The developmental pattern of pulmonary alveoli in rabbits is similar to that in humans. Method: Fetal rabbits were taken out from female rabbits on the 28th day of pregnancy (full term = 31 days) by cesarean section (c‐section). The fetal rabbits were divided into four groups: control (normal saline, NS), budesonide (budesonide, BUD), calf pulmonary surfactant for injection (pulmonary surfactant, PS), and calf pulmonary surfactant + budesonide for injection (pulmonary surfactant + budesonide, PS + BUD). All premature rabbits were kept warm after c‐section. After 15‐min autonomous respiration, a tracheal cannula was implemented for instilling NS, BUD, PS, and PS + BUD. The morphology of lung tissues of premature fetal rabbits was analyzed using optical and electron microscopes. Surfactant protein B (SP‐B) mRNA and protein levels in lung tissues were determined using polymerase chain reaction and Western blotting, respectively. Result: Intratracheal instillation of BUD could increase the alveolar area of the fetal rabbits ( P  < 0.01), decrease the alveolar wall thickness ( P  < 0.01), and increase the mean density of lamellar bodies ( P  < 0.05) and SP‐B protein levels in type II epithelial cells of pulmonary alveoli ( P  < 0.05). Conclusion: Intratracheal instillation of BUD during early postnatal life is effective in promoting alveolarization and increasing SP‐B expression, the pro‐pulmonary maturity of BUD combined with PS is superior to that of BUD or PS alone. However, the long‐term effect of BUD on lung development needs further exploration.